Prophylaxis, diagnosis, and treatment of Traveler’s diarrhea - Al-Ghamdi, Hamed Saeed; Altokhy, Abdulrahman Hamza; Jalalah, Nawal Hussain Bin; Aldukhi, Dhiyaa Hassan; Almalki, Naif Ayidh; Alahmari, Saad Abdullah; Harir, Alaa Ahmed; Ahmed, Manar Salah; Alghamdi, Abdulrahman Hafidh; Alzahimi, Wafa Ibrahim; Altuwaijri, Abdulmohsin Mohammed (International Journal Of Community Medicine And Public Health, 2021)
Evidence still indicates that traveler’s diarrhea might have unpleasant consequences over the affected patients’ time and health, and can increase the frequency of hospitalization and other health-related parameters. As a result of the newly developing serious issues about the resistance of bacteria to the different antibiotics, the management guidelines of traveler’s diarrhea are frequently changing based on this new data to ensure that proper management is delivered to the affected patients and enhance the healthcare practices. In the present literature review, we have discussed the diagnosis, treatment, and prophylaxis against traveler’s diarrhea based on evidence from the current investigations in the literature. The diagnosis of the condition is mainly based on the presence of symptoms suggestive of gastroenteritis, and having a travel history to an endemic country. Besides, cultures might be needed in certain situations to indicate the diagnosis, especially among resistant cases. The best prophylactic approach is to enhance the eating and drinking practices when travelling to endemic countries, in addition to the frequent washing of ingested food by clean water that is obtained from a safe source. The administration of antibiotics is not always recommended, and only moderate and severe cases should be indicated to receive antibiotics based on their clinical evaluation. The administered antibiotics should be based on the resistance and safety profiles among each country to enhance the efficacy of these antibiotics and obtain favorable outcomes.